Permanent land use and microbial contributions shape soil organic carbon stabilization in lake floodplains - Toky Jeriniaina Rabearison; Jim Félix-Faure; François Guillemette; Michelle Garneau; Christine Martineau; Louis Astorg; Martin Chantigny; Virginie Favreau; Jessika Malko; Alexandre Roy; Vincent Maire (Soil Biology and Biochemistry, 2026)

Assessing the effects of urban effluent pollution on freshwater biodiversity and community networks using eDNA metabarcoding - Mélanie Dominique; Magali Houde; Louis Astorg; Jennifer Pham; Susanne Kraemer; Andrée Gendron; Sébastien Sauvé; Maude Lachapelle; Conrad Beauvais; Zofia E. Taranu (Science of The Total Environment, 2025)

Density-dependent effects of exotic brook trout on aquatic communities in mountain lakes revealed by environmental DNA and morphological taxonomy - Daphné Trépanier-Leroux; Matthew C. Yates; Louis Astorg; Dylan J. Fraser; Shelley Humphries; Melania E. Cristescu; Alison M. Derry (Hydrobiologia, 2024)

Freshwater fishes maintain multi‐trait phenotypic stability across an environmental gradient in aqueous calcium - Sarah Sanderson; Louis Astorg; Grant E. Haines; Sandrine Beaumont‐Courteau; R. Brian Langerhans; Alison M. Derry; Andrew P. Hendry (Journal of Fish Biology, 2023)
Reductions in a limiting nutrient might be expected to necessitate compromises in the functional traits that depend on that nutrient; yet populations existing in locations with low levels of such nutrients often do not show the expected degradation of functional traits. Indeed, logperch ( Percina caprodes ), pumpkinseed sunfish ( Lepomis gibbosus ) and yellow perch ( Perca flavescens ) residing in low‐calcium water in the Upper St. Lawrence River were all previously found to maintain levels of scale calcium comparable to those of conspecific populations in high‐calcium water. Yet it remains possible that the maintenance of one functional trait (i.e., scale calcium) under nutrient‐limited (i.e., low calcium) conditions could come at the expense of maintaining other functional traits that depend on the same nutrient. The present study therefore examines other calcium‐dependent traits, specifically skeletal element sizes and bone densities in the same fish species in the same area. Using radiographs of 101 fish from the three species across four locations (two in high‐calcium water and two in low‐calcium water), this new work documents multi‐trait “homeostasis” along the gradient of water calcium. That is, no effect of calcium regime (low‐calcium vs. high‐calcium) was detected on any of the measured variables. Further, effect sizes for the skeletal traits were very low − lower even than effect sizes previously documented for scale calcium. These results thus show that native fishes maintain phenotypic stability across a suite of functional traits linked to calcium regulation, perhaps pointing to an “organismal‐level homeostasis” scenario rather than a “trait‐level homeostasis” scenario.

Different refuge types dampen exotic invasion and enhance diversity at the whole ecosystem scale in a heterogeneous river system - Louis Astorg; Sarah Sanderson; Virginy Côté-Gravel; Freedom Sorbara; Matthew J. S. Windle; Andrew P. Hendry; Alison M. Derry (Biological Invasions, 2021)